miR-155 Promotes ox-LDL-Induced Autophagy in Human Umbilical Vein Endothelial Cells - Zhaozhi Zhang; Xudong Pan; Shaonan Yang; Aijun Ma; Kun Wang; Yuan Wang; Ting Li; Shihai Liu (Hindawi Limited, 2017)
As an evolutionarily conserved metabolic process, autophagy is involved in the process of atherosclerosis (AS). MicroRNA-155 (miR-155), a multifunctional miRNA, plays an important role in many physiological and pathological conditions, including AS and autophagy. However, the effect of miR-155 on the regulation of autophagy in endothelial cells has not been reported to date. Therefore, the objective of our study was to investigate the role of miR-155 in autophagy induced by oxidized low-density lipoprotein (ox-LDL) in human umbilical vein endothelial cells (HUVECs). Our results demonstrated that ox-LDL induced autophagy in HUVECs and increased the expression of miR-155 significantly. Overexpression of miR-155 improved autophagic activity, whereas low expression of miR-155 inhibited autophagic activity. Therefore, the data demonstrated that miR-155 has a modulating effect on the autophagy of vascular endothelial cells.